Very high cycle fatigue of surface carburized CrNi steel at variable stress ratio: Failure analysis and life prediction. (June 2018) - Nehila, Abdelhak; Li, Wei; Gao, Ning; Xing, Xinxin; Zhao, Hongqiao; Wang, Ping; Sakai, Tatsuo
Highlights: The compressive stress ratio associated with marked crack closure effect promotes the FGA formation. The inclusion-fisheye and inclusion-FGA-fisheye induced failure mechanisms were elucidated. A VHCF life prediction model involving crack initiation process was proposed. Abstract: High cycle fatigue and very high cycle fatigue properties of a surface-carburized CrNi steel were examined under axial loading with stress ratios of −1 and 0. The positive stress ratio overcomes the effect of carburized layer and promotes crack initiation from the carburized layer. The morphology of fine granular area (FGA) is more distinct under the negative stress ratio with more obvious crack closure effect. Two models concerning the inclusion-fisheye failure and the inclusion-FGA-fisheye failure are proposed. The predicted fatigue lives based on the concept of crack initiation are in good agreement with experimental results.